Genomic characterization of the adolescent idiopathic scoliosis-associated transcriptome and regulome. (12th November 2020) - Makki, Nadja; Zhao, Jingjing; Liu, Zhaoyang; Eckalbar, Walter L; Ushiki, Aki; Khanshour, Anas M; Wu, Joe; Rios, Jonathan; Gray, Ryan S; Wise, Carol A; Ahituv, Nadav
Abstract: Adolescent idiopathic scoliosis (AIS), a sideways curvature of the spine, is the most common pediatric musculoskeletal disorder, affecting 3% of the population worldwide. However, its genetic bases and tissues of origin remain largely unknown. Several genome-wide association studies (GWAS) have implicated nucleotide variants in non-coding sequences that control genes with important roles in cartilage, muscle, bone, connective tissue and intervertebral disks (IVDs) as drivers of AIS susceptibility. Here, we set out to define the expression of AIS-associated genes and active regulatory elements by performing RNA-seq and chromatin immunoprecipitation-sequencing against H3 lysine 27 acetylation in these tissues in mouse and human. Our study highlights genetic pathways involving AIS-associated loci that regulate chondrogenesis, IVD development and connective tissue maintenance and homeostasis. In addition, we identify thousands of putative AIS-associated regulatory elements which may orchestrate tissue-specific expression in musculoskeletal tissues of the spine. Quantification of enhancer activity of several candidate regulatory elements from our study identifies three functional enhancers carrying AIS-associated GWAS SNPs at the ADGRG6 and BNC2 loci . Our findings provide a novel genome-wide catalog of AIS-relevant genes and regulatory elements and aid in the identification of novel targets for AIS causality and treatment.